KINERJA ORGANISASI KOMISI PEMILIHAN UMUM DAERAH (KPUD) KOTA PONTIANAK - Suranto E.21109069, Fajar (PublikA, Jurnal Ilmu Administrasi Negara, 2013)
The problem in this study is the presence of non-voters who figures indicate that the level of performance of the Election Commission of Pontianak is still room for improvement especially in the DPT and socialization fixing elections , and weak elements in the organization's human resources the KPU . HR weakness evident in the matching process and does not research ( coklit ) against voter data by field officers . From the research it was found that the performance of the organization in implementing the Election Commission Pontianak Pontianak governor election in less than optimal it can be seen from the research findings that indicate a short amount of time that is only 5 months to socialize regulation and the establishment of PPK, PPS and KPPS . There are problems in the implementation phase are: short time in preparing and announcing the provisional voter list ( DPS ) , the list of voters ( DP ) additional , permanent voters list ( DPT ) so that voters are less likely to check the list of names of voters in the Village . Responding to phenomena Parliament in granting time for preparation for the elections to the Election Commission will come a time when that should not be too short at only 5 months prior to the expiration of the term of office of Regional Head and Deputy Head . In addition, for the performance of the Election Commission Organization Pontianak more optimal , appropriate personnel who served in the Secretariat of the Commission 's increased investment in its people either through formal and informal education such as training , Bimtek and khursus - khursus skills .Â Keywords : Performance , Organization , National Election Commission